Adult precision medicine: learning from the past to enhance the future. Issue 1 (24th October 2020) - Ghiaseddin, Ashley; Hoang Minh, Lan B; Janiszewska, Michalina; Shin, David; Wick, Wolfgang; Mitchell, Duane A; Wen, Patrick Y; Grossman, Stuart A
Abstract: Despite therapeutic advances for other malignancies, gliomas remain challenging solid tumors to treat. Complete surgical resection is nearly impossible due to gliomas' diffuse infiltrative nature, and treatment is hampered by restricted access to the tumors due to limited transport across the blood–brain barrier. Recent advances in genomic studies and next-generation sequencing techniques have led to a better understanding of gliomas and identification of potential aberrant signaling pathways. Targeting the specific genomic abnormalities via novel molecular therapies has opened a new avenue in the management of gliomas, with encouraging results in preclinical studies and early clinical trials. However, molecular characterization of gliomas revealed significant heterogeneity, which poses a challenge for targeted therapeutic approaches. In this context, leading neuro-oncology researchers and clinicians, industry innovators, and patient advocates convened at the inaugural annual Remission Summit held in Orlando, FL in February 2019 to discuss the latest advances in immunotherapy and precision medicine approaches for the treatment of adult and pediatric brain tumors and outline the unanswered questions, challenges, and opportunities that lay ahead for advancing the duration and quality of life for patients with brain tumors. Here, we provide historical context for precision medicine in other cancers, present emerging approaches for gliomas, discuss their limitations, and outline the steps necessary for future success. We focus on the advances in small molecule targeted therapy, as the use of immunotherapy as an emerging precision medicine modality for glioma treatment has recently been reviewed by our colleagues.